Propuesta estratégica de marketing para el restaurante Barlovento Alta Mar - Yánez Jácome, Emilio Sebastián (2020)
The objective of this degree project is to create a strategic marketing proposal for the Barlovento Alta Mar restaurant, explaining the different tools used to prepare a marketing plan for this business. Chapter one defines the main concepts aligned to the area of food and beverages, as well as describe a brief history of the establishment, considering the work and knowledge of experts in the field, which complement the theory and steps for the development of this research. In the second chapter, the investigation of the macro and microenvironment where Barlovento Alta Mar restaurant is currently located is established. In this way the key points to work for the progress of the strategic proposal are defined. In addition, the opportunities and threats that the business will have when entering new market niches will be fully analyzed, as well as the positive and negative factors for the creation of strategies. Regarding the results in the analysis chapter, the information obtained during the macro and microenvironment research stage will be explained. The profiles of the current and potential customers of the restaurant as well as a competitive analysis of Benchmarking will be further described. Finally, a financial budget has been included, which is necessary for the company to evaluate the costs and expenses during the implementation of the proposed strategies, based on the actions that each department has to execute.